KEPEMIMPINAN KEPALA DESA DALAM MEWUJUDKAN DESA YANG MAJU DAN MANDIRI ( Studi Multisitus pada Desa di Kecamatan Dringu Kabupaten Probolinggo) - Bukhari; Ernani Hadiyati; Sugeng Mulyono (Faculty of Islamic Economics and Business, 2020)
The village head's leadership is very influential on the progress of the village. Good village governance and quality village officials are able to bring villages to become independent in improving the welfare of village communities. Qualitative research with a multi-site method is needed to obtain in-depth information about the style and strategy, triggers and inhibiting factors, as well as the expectations of the leadership of the village head in the Dringu Subdistrict, Probolinggo Regency. A qualitative method with a multi-site approach was used in this study. This design was carried out guided by 3 stages of phenomenology, namely the intuitive stage, bracketing, analyzing and doing descriptive and interpretation. Unstructured interviews are used as the main method of data collection. There are 10 participants who have been saturated and based on participant criteria. The results of the study found 3 themes, namely (1) Leadership of innovative progressive and visioner village heads; (2) The duties and responsibilities of the village head are full time; (3) Hope to be an independent and participatory village. Keywords: Leadership, Village Head, developed and independent villages.